2020
DOI: 10.1038/s41467-020-14989-4
|View full text |Cite
|
Sign up to set email alerts
|

A signal cascade originated from epidermis defines apical-basal patterning of Arabidopsis shoot apical meristems

Abstract: In multicellular organisms, a long-standing question is how spatial patterns of distinct cell types are initiated and maintained during continuous cell division and proliferation. Along the vertical axis of plant shoot apical meristems (SAMs), stem cells are located at the top while cells specifying the stem cells are located more basally, forming a robust apical-basal pattern. We previously found that in Arabidopsis SAMs, the HAIRY MERISTEM (HAM) family transcription factors form a concentration gradient from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 48 publications
3
71
0
Order By: Relevance
“…Under the control of the endogenous HAM1 promoter and 3' terminator, the YPET-HAM1 protein is not expressed in the epidermal L1 layer, barely expressed in the L2 layer, and highly expressed in the rib meristem and peripheral zone of the corpus ( Figures 1A-F). In parallel, we imaged the pHAM2::YPET-HAM2 translational reporter (Zhou et al, 2015;Zhou et al, 2018;Han et al, 2020b) in the ham123 SAM (Figures 2A-C). pHAM2:: YPET-HAM2 is highly expressed in the rib meristem and peripheral zone of the corpus, but it is repressed or completely off in the L1 and L2 layers (Figures 2A-F), a pattern comparable to that of pHAM1::YPET-HAM1 ( Figures 1A-F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the control of the endogenous HAM1 promoter and 3' terminator, the YPET-HAM1 protein is not expressed in the epidermal L1 layer, barely expressed in the L2 layer, and highly expressed in the rib meristem and peripheral zone of the corpus ( Figures 1A-F). In parallel, we imaged the pHAM2::YPET-HAM2 translational reporter (Zhou et al, 2015;Zhou et al, 2018;Han et al, 2020b) in the ham123 SAM (Figures 2A-C). pHAM2:: YPET-HAM2 is highly expressed in the rib meristem and peripheral zone of the corpus, but it is repressed or completely off in the L1 and L2 layers (Figures 2A-F), a pattern comparable to that of pHAM1::YPET-HAM1 ( Figures 1A-F).…”
Section: Resultsmentioning
confidence: 99%
“…Vegetative shoots were fixed with 4% paraformaldehyde overnight at 4°C. Tissues were embedded, sectioned, hybridized and washed as described previously ( Krizek, 1999 ; Han et al, 2020b ). The CLV3 probe was described previously ( Zhou et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The epidermis not only provides mechanical restriction to inner tissues, but also serves as a source of biochemical signals that directs development (Chickarmane et al 2012;Knauer et al 2013;Gruel et al 2016;Han et al 2020). ATML1 and PDF2 are key regulators of epidermal cell differentiation, and the atml1 pdf2 mutants are expected to lose, at least partially, both mechanical restriction and epidermisderived biochemical signals (Abe et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The epidermis also influences pattern formation in the shoot apical meristem (SAM), as several reports have suggested that certain microRNAs (miRNAs), generated in the outermost cell layer of the SAM, form an inhibitory gradient that contributes to the positioning of the stem cell niche at away from the epidermis [7,8]. Consistently, epidermal deficient mutants often show ectopic SAM activity in the leaves [9].…”
Section: Epidermis Formation and Its Role In Plant Developmentmentioning
confidence: 99%